Association between physical activity and functional and cognitive status in nonagenarians: results from the Mugello study. (June 2019) - Pancani, Silvia; Vannetti, Federica; Sofi, Francesco; Cecchi, Francesca; Pasquini, Guido; Fabbri, Laura; Mosca, Irene Eleonora; Macchi, Claudio; ,
ABSTRACT: This study aimed at assessing daily physical activity and its relationship with functional and cognitive status in nonagenarians. Cross-sectional study. 167 nonagenarians (124 women and 43 men, mean age 92 years ± 3) who participated in the Mugello study. Participants underwent daily step count through the SenseWear armband, which was considered as an indicator of physical activity. Other main variables were: handgrip strength, gait speed, depression, cognitive status and quality of life. The median value of steps per day was 883 and 658 in women and men, respectively, with a participant, in the women group, showing values up to 10, 000. After adjusting for potential confounders, physical activity remained a significant positive correlate of handgrip strength (r = 0.4), gait speed (r = 0.8), and cognitive status (r = 0.6 and 0.8, respectively for raw scores and for scores adjusted for age and education). On the contrary, physical activity remained a significant negative correlate of depression (r = 0.5). Our results provide quantitative information on daily physical activity and show a significant relationship between daily physical activity and functional and cognitive status in nonagenarians.